Mental health problems in adolescents with cochlear implants: peer problems persist after controlling for additional handicaps - Huber, Maria; Burger, Thorsten; Illg, Angelika; Kunze, Silke; Giourgas, Alexandros; Braun, Ludwig; Kroeger, Stefanie; Nickisch, Andreas; Rasp, Gerhard; Becker, Andreas; Keilmann, Annerose (Frontiers in Psychology, 2015)
The aims of the present multi-center study were to investigate the extent of mental health problems in adolescents with a hearing loss and cochlear implants (CIs) in comparison to normal hearing (NH) peers and to investigate possible relations between the extent of mental health problems of young CI users and hearing variables, such as age at implantation, or functional gain of CI. The survey included 140 adolescents with CI (mean age = 14.7, SD = 1.5 years) and 140 NH adolescents (mean age = 14.8, SD = 1.4 years), their parents and teachers. Participants were matched by age, gender and social background. Within the CI group, 35 adolescents were identified as “risk cases” due to possible and manifest additional handicaps, and 11 adolescents were non-classifiable. Mental health problems were assessed with the Strengths and Difficulties Questionnaire (SDQ) in the versions “Self”, “Parent”, and “Teacher”. The CI group showed significantly more “Peer Problems” than the NH group. When the CI group was split into a “risk-group” (35 “risk cases” and 11 non-classifiable persons) and a “non-risk group” (n = 94), increased peer problems were perceived in both CI subgroups by adolescents themselves. However, no further differences between the CI non-risk group and the NH group were observed in any rater. The CI-risk group showed significantly more hyperactivity compared to the NH group and more hyperactivity and conduct problems compared to the CI non-risk group. Cluster analyses confirmed that there were significantly more adolescents with high problems in the CI-risk group compared to the CI non-risk group and the NH group. Adolescents with CI, who were able to understand speech in noise had significantly less difficulties compared to constricted CI users. Parents, teachers, and clinicians should be aware that CI users with additionally special needs may have mental health problems. However, peer problems were also experienced by CI adolescents without additional handicaps